Cellular behaviour of bone marrow stromal cells on modified Ti-Nb surfaces. (15th February 2018) - Ureña, J.; Tsipas, S.; Jiménez-Morales, A.; Gordo, E.; Detsch, R.; Boccaccini, A.R.
Highlights: The surface modification of titanium by niobium diffusion leads to cell viability values similar to bare titanium. Ti-Nb surfaces increased the specific level of lactate dehydrogenase activity of Ti twice, indicating cell differentiation. Bone-like nodules were deposited by stromal cells on the modified Ti-Nb surfaces indicating bone mineralization. Graphical abstract: Image 1 Abstract: The cellular behaviour of bone marrow stromal cells on titanium surfaces modified by niobium diffusion is presented in order to test their osteogenic differentiation response after culturing for 21 days. The surface modification of Ti substrates produced by powder metallurgy was performed through niobium diffusion treatments. Ti-Nb exhibited a β-Ti surface together with a microstructural (β / α + β / α) and compositional (Ti-Nb) gradient which enhances hardness, wear resistance and lowers the elastic modulus making it more similar to the human bone. Furthermore, the Ti-NbNH4Cl by means of the activating agent achieved three times the hardness of Ti together with a porous surface. The in vitro osteogenic differentiation response of bone marrow stromal cells on both Ti-Nb surfaces indicated the positive cell-material interaction. The osteogenic differentiation of cells was successful after 21 days, considering the positive response in terms of increased cell viability, lactate dehydrogenase-(LDH) activity, alkaline phosphatase-(ALP) activity expression (osteogenic marker) and bone-like nodules deposition by ST-2 cells as a bone mineralization cue. Therefore, the positive effect of a low elastic modulus Ti-Nb surface and a porous nitride Ti-NbNH4Cl with suitable wettability and average roughness values on the osteogenic differentiation response of bone marrow stromal cells is demonstrated.